West Africa - Mineral Sector Strategic Assessment (WAMSSA) : An Environmental and Social Strategic Assessment for the Development of the Mineral Sector in the Mano River Union - World Bank (World Bank, 2012)
The West African Mineral Sector Strategic Assessment (WAMSSA) is a strategic environmental and social assessment intended to identify policy, institutional, and regulatory adjustments required to integrate environmental and social considerations into mineral sector development in Africa. The study focused on three Mano River Union (MRU) countries, Guinea, Liberia, and Sierra Leone, all categorized as mineral-rich countries which earn - or could earn (in the case of Liberia) - significant revenues from exports of bauxite, iron ore, rutile, gold, and diamonds. WAMSSA featured an analytical component, and an extensive consultation process designed to initiate a policy dialogue on improving mineral sector governance and enhancing the benefits of mineral sector development for the MRU region. This report summarizes the findings of the WAMSSA process, and provides a series of recommendations to address environmental, social, and governance priorities highlighted by analytical and consultation components of the assessment. The recommendations are intended to provide guidance to the African Mineral Governance Program (AMGP) and Extractive Industry Transparency Initiative Plus Plus initiatives that are gathering momentum in the region.